Transformational Leadership and Creative Performance: A Dyadic Analysis of Salespeople and Their Supervisors - Alén, Elisa; Banerjee, Bidisha; Gupta, Bhumika (Asian Journal of Business and Accounting, 2017)
Manuscript type: Research paper Research aims: This paper examines the impact of transformational leadership on salespersons in India by focusing on how transformational leadership affects their creative performance, intrinsic motivation as well as trust towards their supervisors. Design/ Methodology/ Approach: This study analyses the dyadic data of 120 employees and their supervisors working in companies in India. Structural equation modelling was used to test the relationship between transformational leadership and salespersons’ creative performance, intrinsic motivation and trust. Research findings: Results suggest that transformational leadership is positively related to salespersons’ creative performance and their intrinsic motivation. On the contrary, intrinsic motivation does not influence creative performance. Findings also demonstrate the connection between transformational leadership and trust in supervisor. Theoretical contributions/ Originality: This study expands on previous works by looking at creativity in the sales context. Despite the widespread interest in this field, findings of prior studies have been inconclusive, suggesting the existent of a mediator. This study thus fill the gap by providing additional evidence of how intrinsic motivation and trust in supervisor mediates the relationship between transformational leadership and creative performance. Practitioner/ Policy Implications: The findings of this study suggest that there is an imperative need for leaders (such as managers or supervisors) to stimulate the creativity of salespersons so as to boost organisational goals. Research limitations/ Implications: Future studies may be conducted on a larger and more diverse samples, involving employees working in other industries and countries.